General practitioners’ perceptions of best practice care at the end of life: a qualitative study - Herrmann, Anne (BJGP Open, 2019)
BACKGROUND: GPs can play a central role in palliative care delivery. However, little is known about their views on what constitutes best practice care at the end of life. AIM: To explore, in a sample of Australian GPs, their perceptions of best practice palliative care and their ideal role in its delivery. DESIGN & SETTING: A qualitative interview study of 25 GPs practising in metropolitan and non-metropolitan locations in New South Wales, Australia. METHOD: Semi-structured telephone interviews were conducted. Data were analysed using qualitative content analysis. RESULTS: Participants had a mean age of 51 years, and had practised between 3 and 38 years (mean 19 years). Best practice palliative care was perceived to be proactive and responsive to a wide range of patient and family needs. Many participants indicated a need for relational continuity, which involves GPs establishing a care pathway from diagnosis to palliation, coordinating care across the pathway, and collaborating with other healthcare providers. A number of participants perceived palliative care as a natural extension of primary care and indicated that best practice palliative care mainly requires experiential knowledge and good communication skills, rather than specialised medical knowledge. Participants listed a number of communication strategies to offer patients and their families choice and ongoing negotiation about the recommended treatments. CONCLUSION: This study provides novel in-depth insights into GPs’ perceptions of best practice palliative care. Future research should further investigate the identified features of care, and whether they can maximise the outcomes of patients and their families.